Social Values in the Activities of the Regional Disaster Management Agency (RDMA) in Banjar Regency - Nursahid Nursahid; Syaharuddin Syaharuddin; Rusmaniah Rusmaniah; Ersis Warmansyah Abbas; Sigit Triyono (Universitas Lambung Mangkurat, 2024)
The objective of this study is to identify social values associated with the operations of the Banjar Regency Regional Disaster Management Agency (RDMA). This research was conducted through a qualitative approach. The research subjects were individuals involved in RDMA activities in Banjar Regency, focusing on the pre-disaster, emergency response, and post-disaster stages. After being collected through observation, interviews, and documentation, the data was analyzed through simplification, presentation, and conclusion. As a result of the research, the RDMA of Banjar Regency carries out disaster management activities in several stages, namely pre-disaster, emergency response, and post-disaster. The social values contained in the RDMA activities in Banjar Regency include responsibility, care, helping, discipline, and cooperation. The findings show that the RDMA of Banjar Regency plays an important role in maintaining the safety and welfare of the community in its region, by paying attention to the underlying social values. The hope of this research is to provide a deeper insight into the role of RDMA in disaster management and its contribution to the development of a safer and more resilient community in Banjar District.